The QUALITY OF PAYMENT SERVICES FOR RETIRED CIVIL SERVANTS AT PT. TASPEN (PERSERO) PONTIANAK BRANCH: Bahasa indonesia - Zeny Izam Zaini; Kristina Olivia Radius; Nur Ramadhana; Anny Riwayati (Yayasan Wayan Marwan Pulungan, 2024)
In realizing the improvement of the welfare of Civil Servants (PNS) as state officials and public servants who have the potential to greatly determine the smooth implementation of development, the government has established a system that can protect Civil Servants and improve the welfare of Civil Servants and their families. Namely with the issuance of PP. No. 10 of 1963 concerning Savings and Insurance for Civil Servants and pensions to guarantee and improve the welfare of Civil Servants in their old age. The method used in this study is a qualitative research method, so data analysis is carried out systematically, examining the problems under study, regulations, or programs that are related to the material and also using interviews and observations or observations by first making interview guidelines. The results of this research show that the Quality of Administration Services for Civil Servant Pension Payments PT. TASPEN (Persero) Pontianak Branch Office to participants and recipients TASPEN has been running well.